PENGARUH INSTRUMEN KEBIJAKAN MAKROPRUDENSIAL TERHADAP LIKUIDITAS BANK UMUM SYARIAH - Aisiyah Rahma; Nurbaiti Nurbaiti; Muhammad Syahbudi (Fakultas Ekonomi Bisnis Islam, 2023)
This research is to determine the effect of macroprudential instruments on the liquidity of Islamic commercial banks. The instruments used were Minimum Statutory Reserves (MSR) and Sharia Macroprudential Liquidity Buffer (MLB Sharia) as instruments that experienced changes in value during the study period. Liquidity is calculated using the Sharia Macroprudential Intermediation Ratio (Sharia MIR) instrument. This research uses a quantitative approach with secondary data sources. The type of data uses panel data with eViews 9 data processing software. The research sample consisted of six Islamic commercial banks in Indonesia, namely Bank Muamalat, BCA Syariah, Bank Victoria Syariah, Bank Panin Dubai Syariah, BJB Syariah, and BTPN Syariah with the 2018-2021 period. The study used panel data regression analysis, namely the random effect model. The results state that the MSR variable has a negative and significant effect on liquidity, the MLB Sharia variable has a positive and significant effect on liquidity and simultaneously the MSR and MLB Sharia variables have a significant effect on Islamic commercial bank liquidity.